PERBANDINGAN NILAI MOST PROBABLE PRODUCING ABILITY KAMBING ETAWAH ANATAR KECAMATAN METRO SELATAN DAN METRO BARAT, KOTA METRO - Deni Rinaldi; Idalina Harris; Novirzal . (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The Most Probable Producing Ability (MPPA) value is a maximum estimation of doe Etawahcrossbred reproduction ability. The objective of this research was to find out the differences of MPPAof Etawah goat breeding between South Metro and West Metro sub districts. This was a surveyresearch method to obtain research materials from 30 doe Etawah crossbred in each sub district thathad same age records when they gave birth their kid, and records of kid from their doe Etawahcrossbred samples including birth weight, type of birth, type of raising, body weight at weaning. Theresults showed that the difference values obtained between South Metro and West Metro were2.48±0.06 kg and 2.55±0.07 kg respectively for average birth weights; 20.18±0.64 kg and 21.10±0.85kg respectively for corrected weaning body weight; 0.49 : 0.37 respectively for repeatability value ofweaning body weight; 20.18±0.42 and 21.10±0.46 for average value of MPPA of weaning bodyweight respectively. The t-student test results showed that the values of corrected body weight andMPPA of Etawah crossbred in this research were the same (P≤0.05).